2018
DOI: 10.1111/nph.15283
|View full text |Cite
|
Sign up to set email alerts
|

Plant carbon metabolism and climate change: elevated CO2 and temperature impacts on photosynthesis, photorespiration and respiration

Abstract: Contents Summary 32 I. The importance of plant carbon metabolism for climate change 32 II. Rising atmospheric CO2 and carbon metabolism 33 III. Rising temperatures and carbon metabolism 37 IV. Thermal acclimation responses of carbon metabolic processes can be best understood when studied together 38 V. Will elevated CO2 offset warming-induced changes in carbon metabolism? 40 VI. No plant is an island: water and nutrient limitations define plant responses to climate drivers 41 VII. Conclusions 42 Acknowledgemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
454
7
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 717 publications
(557 citation statements)
references
References 273 publications
23
454
7
3
Order By: Relevance
“…Respiration and photosynthesis may acclimate to temperature together such that their ratio ( R/A ) is constant. This is consistent with some measurements of an invariant R/A ratio across a wide range of temperatures, but with some additional variation at exceptionally high or low temperatures (Atkin et al ., ; Aspinwall et al ., ; Slot & Winter, ; Crous et al ., ; Dusenge et al ., ). Importantly, several studies indicated that the R/A ratio changed in response to a change in growth temperature, but that a homeostatic R/A ratio was restored following the development of new leaves (Ziska & Bunce, ; Loveys et al ., ; Campbell et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Respiration and photosynthesis may acclimate to temperature together such that their ratio ( R/A ) is constant. This is consistent with some measurements of an invariant R/A ratio across a wide range of temperatures, but with some additional variation at exceptionally high or low temperatures (Atkin et al ., ; Aspinwall et al ., ; Slot & Winter, ; Crous et al ., ; Dusenge et al ., ). Importantly, several studies indicated that the R/A ratio changed in response to a change in growth temperature, but that a homeostatic R/A ratio was restored following the development of new leaves (Ziska & Bunce, ; Loveys et al ., ; Campbell et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, increased CO 2 effects on tree growth remain poorly understood (Dusenge et al. ) and may be less important for seedlings than mature trees (Johnson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of future changes in air and leaf temperature on plant C balance may alter productivity (Boisvenue & Running, ; Reyer et al, ; Teskey et al, ; Zhao et al, ) and eventually lead to shifts in species ranges and local extinctions (Chen, Hill, Ohlemüller, Roy, & Thomas, ; Loarie et al, ). Given the close coupling between T l and plant productivity, quantifying vegetation responses to climatic changes requires an understanding of leaf‐level responses to temperature and thermal fluctuations (Dusenge, Duarte, & Way, ).…”
Section: Introductionmentioning
confidence: 99%